The Influence of Service Quality, Facilities and Prices on Visitor Satisfaction at the Gajah Mungkur Reservoir Tourism Object, Wonogiri Regency - Rahmatika Nur Utami; Laksono Sumarto; Zandra Dwanita Widodo (International Journal of Economics, Commerce, and Management, 2024)
Study This aim For knowing : (1) Influence quality service to satisfaction visitors , (2) Influence facility to satisfaction visitors , (3) Influence price to satisfaction visitors , (4) Influence quality services , facilities , and price to satisfaction visitors . Study This manifold quantitative with use type of primary data. Testing analysis data quality using test validity And test reliability . Technique analysis of the data used is multiple linear regression . Study This use purposive sampling method where samples taken​ is from consideration data certain Where generally customized with objective And problem study And sample in study This totaling 100 respondents who are visitors Object Tour Gajah Mungkur Reservoir Regency Wonogiri . Technique deep data collection study This with spread questionnaire with scale likert to respondents . Results study This in a way t test shows that each variable quality services , facilities , and price in a way Partial own influence positive And significant to satisfaction visitors Object Tour Gajah Mungkur Reservoir Regency Wonogiri . As well as, deep F test shows that variable quality services , facilities , and price in a way simultaneous own influence positive And significant to satisfaction​ visitors Object Tour Gajah Mungkur Reservoir Regency Wonogiri . Whereas results test coefficient determination R 2 own mark Adjusted R Square is 70.2 % which means variable satisfaction visitors influenced by existing variables​ on study This And the remaining 29.8% is affected by other variables outside study